2015
DOI: 10.1049/iet-epa.2013.0340
|View full text |Cite
|
Sign up to set email alerts
|

Implementation of a sensorless interior permanent magnet synchronous drive based on current deviations of pulse‐width modulation switching

Abstract: This study proposes a rotor position estimating method by detecting the stator currents under each pulse-width modulation switching state for an interior permanent magnet synchronous motor drive system. The proposed sensorless motor drive system can be applied in an air conditioner without injecting any high-frequency sinusoidal or cosine voltage signal. The operating speed range can be effectively extended because the maximum available voltage is increased when compared to the high-frequency sinusoidal or cos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 33 publications
(70 reference statements)
0
14
0
Order By: Relevance
“…. One can immediately select the (N − 1) switching sates in (9) due to the descending reference order. Further, if the corresponded duty ratios are denoted as…”
Section: General Solution Of N-phase Vsi Systemswitching Statesmentioning
confidence: 99%
See 1 more Smart Citation
“…. One can immediately select the (N − 1) switching sates in (9) due to the descending reference order. Further, if the corresponded duty ratios are denoted as…”
Section: General Solution Of N-phase Vsi Systemswitching Statesmentioning
confidence: 99%
“…Voltage source inverters (VSIs) are widely utilised in driving the variable speed ac motors. Pulse width modulations (PWM) such as single carrier sinusoidal PWM (SPWM) [1], zero-sequence injection PWM [2], space-vector PWM (SVPWM) [3][4][5][6][7] and neural-network based SVPWM [8] have been proposed to generate the control commands of 3-phase VSI and applied to sensorless motor drive [9]. Further, multiphase PWMs are proposed due to the advantages of increased efficiency [10], reduced torque pulsation, lower dc link current harmonics, improved fault tolerance [11,12] and lower power handling requirement of power switches [3].…”
Section: Introductionmentioning
confidence: 99%
“…Chen et al [24] demonstrated the implementation of high-performance sensorless IPM motor. Literature on sensorless control is available in [25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…For achieving high-performance current control of permanent magnet synchronous motors (PMSMs), accurate information of rotor position is usually required. In practice, the positionsensorless operation is preferred in hostile environments and lowcost applications [17,18]. Even equipped with a position sensor, a rotor position estimator is still required to achieve sensor faulttolerant control for safety or reliability reasons in some cases, such as in automotive applications [19].…”
Section: Introductionmentioning
confidence: 99%